2013
DOI: 10.1159/000351247
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nicorandil in Neuroprotective Activation of PI3K/AKT Pathways in a Cellular Model of Alzheimer's Disease

Abstract: Nicorandil, an ATP-sensitive potassium (KATP) channel opener, is known to have protective effects on ischemic injury in heart and brain. One of the most important protective mechanisms is the anti-apoptotic effect on cardiomyocytes and neurons. This study explored the anti-apoptotic effect of nicorandil against neurotoxicity in SH-SY5Y cells overexpressing the Swedish mutant APP (APPsw) and the possible mechanisms involved. We used SH-SY5Y cells transiently transfected with APPsw as a cellular model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 78 publications
2
18
0
Order By: Relevance
“…For instance, Cuie et al has shown that the level of pAkt is decreased in the APP/PS1 transgenic model of AD (Cui et al 2013). Similarly, the reduced level of activated Akt is also reported in a cellular model of AD (neurotoxicity in SH-SY5Y cells overexpressing the Swedish mutant APP) (Kong et al 2013). Our results support the latter as the amount of pAkt was decreased in Aβ-treated cells.…”
Section: Discussionsupporting
confidence: 89%
“…For instance, Cuie et al has shown that the level of pAkt is decreased in the APP/PS1 transgenic model of AD (Cui et al 2013). Similarly, the reduced level of activated Akt is also reported in a cellular model of AD (neurotoxicity in SH-SY5Y cells overexpressing the Swedish mutant APP) (Kong et al 2013). Our results support the latter as the amount of pAkt was decreased in Aβ-treated cells.…”
Section: Discussionsupporting
confidence: 89%
“…It has been welldocumented that the Akt signaling pathway is essential for neuronal survival in cortical neurons in vitro. Evidence from other studies has also demonstrated a decrease in Akt activity in animals and cellular models of AD [49,50]. Our results demonstrate that maintenance of high megalin expression levels prevents Ab42induced disruption of Akt phosphorylation.…”
Section: Discussionsupporting
confidence: 82%
“…Bcl2 protects neuronal cells by inhibiting the activation of caspase-3 81,82. Previously, Bcl-2 expression was shown to be upregulated, while Bax and caspase-3 were down regulated in AD models 83. Bax also plays an essential role in oligomeric Aβ-induced neuronal cell death 84.…”
Section: Discussionmentioning
confidence: 99%